Is there a role for procalcitonin in differentiating uncomplicated and complicated diverticulitis in order to reduce antibiotic therapy? A prospective diagnostic cohort study - Victor Jeger; Roxana Pop; Farschad Forudastan; Jean Pierre Barras; Markus Zuber; Rein Jan Piso (Swiss Medical Weekly, 2017)
AIMS OF THE STUDY